Nanostructured biomaterials for overcoming biological barriers - Alonso, Maria Jose 534239; Csaba, Noemi S. 534240; Royal Society of Chemistry (Great Britain) 7371 (Cambridge : RSC Publishing)
Includes bibliographical references and index